Penggunaan Terminologi dan Komunikasi Kesehatan dalam Pemberitaan #HIVAIDS - Lartutul, Xavery Alberto; Mulyana, Deddy; Hadisiwi, Purwanti (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The issue of HIV and AIDS is not only a health concern but also a social one, heavily influenced by how the media communicates it to the public. This study aims to examine the use of terminology and health communication practices in news coverage about HIV and people living with HIV on the online platform harianjogja.com during the period of February 2024 to June 2025. The research employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis model. Data were collected through documentation of news texts published within the specified period, then analyzed by examining the three dimensions of Fairclough’s framework: text, discourse practice, and social practice. The findings reveal that the news coverage remains dominated by terminology inconsistent with the UNAIDS Terminology Guidelines 2015, such as “AIDS sufferers” and “deadly virus.” The language used in the news texts tends to frame people living with HIV as objects of suffering or sources of moral threat. Editorial practices are frequently driven by considerations of audience appeal and clickbait dynamics, which in turn undermine empathetic perspectives and a human rights oriented framework.Such reporting potentially reinforces stigma, weakens public empathy, and hinders progress toward achieving the global Three Zero HIV 2030 targets. This study underscores the urgency of transforming health journalism toward a more humanistic, inclusive, and equitable approach through cross-sectoral collaboration, including with affected communities. Abstrak Isu HIV dan AIDS tidak hanya menjadi permasalahan kesehatan, tetapi juga isu sosial yang sangat dipengaruhi oleh cara media mengkomunikasikannya kepada publik. Penelitian ini bertujuan untuk mengkaji penggunaan terminologi dan praktik komunikasi kesehatan dalam pemberitaan mengenai HIV dan orang yang hidup dengan HIV di media daring harianjogja.com selama periode Februari 2024 hingga Juni 2025. Penelitian ini menggunakan pendekatan kualitatif dengan metode Analisis Wacana Kritis model Norman Fairclough. Data dikumpulkan melalui dokumentasi teks berita yang dipublikasi pada periode tersebut, kemudian dianalisis dengan menelaah tiga dimensi analisis Fairclough: teks, praktik wacana, dan praktik sosial. Hasil penelitian menunjukkan bahwa pemberitaan masih didominasi oleh istilah yang tidak sesuai dengan pedoman UNAIDS Terminology Guidelines 2015, seperti penderita AIDS dan virus mematikan. Bahasa yang digunakan dalam teks berita cenderung membingkai orang yang hidup dengan HIV sebagai objek penderitaan atau sumber ancaman moral. Praktik redaksional sering dibentuk oleh orientasi pada daya tarik publik dan logika klikbait, sehingga mengorbankan perspektif empatik dan pendekatan berbasis hak asasi manusia. Pemberitaan semacam ini berpotensi memperkuat stigma, melemahkan empati publik dan menghambat pencapaian target global Three Zero HIV 2030. Penelitian ini menegaskan urgensi transformasi jurnalisme kesehatan menuju pendekatan yang lebih humanistik, inklusif, dan adil melalui kolaborasi lintas sektor, termasuk komunitas terdampak.